Are Dietary Amino Acids or Protein Quality Associated with Infant Length Gain from 6 to 12 Months in Rural Malawi? (P10-010-19). (13th June 2019) - Matchado, Andrew; Dewey, Kathryn; Stewart, Christine; Ashorn, Per; Ashorn, Ulla; Maleta, Kenneth; Hemsworth, Jaimie; Kumwenda, Chiza; Arnold, Charles
Abstract: Objectives: 1) to estimate the probability of inadequate amino acid intake among infants 9–10 months of age in rural Malawi 2) to evaluate whether dietary amino acid intake or protein quality are associated with length gain from 6 to 12 months of age Methods: We assessed total amino acid intake from breast milk and complementary foods in 285 infants. Breast milk intake and complementary foods were estimated using dose-to-mother deuterium oxide dilution method and repeat 4-pass interactive 24-hour recall interviews, respectively. Amino acid composition values were taken from FAO human milk profile, Tanzania Food Composition table and International Minilist. Protein quality was estimated using Digestible Indispensable Amino Acid Score (DIAAS). Probability of intake below Estimated Average Requirement (EAR) for each amino acid was estimated using National Cancer Institute (NCI) method. We estimated protein quality of complementary food using median DIAAS. We assumed a DIAAS of ≥0.75 to represent a diet or food with good protein quality. Relationships between amino acid intake or protein quality with length gain were assessed using regression models. Length was measured at 6 and 12 months of age and length for age z-score (LAZ) velocity was calculated (ΔLAZ/months). Results: The probability of inadequate amino acid intake from breast milk and complementary food that included a lipid-based nutrient supplement (LNS) was 3% for lysine, 0% for tryptophan, threonine, valine, histidine, isoleucine, leucine, sulfur containing amino acids (SAA), and aromatic amino acids (AAA). Without LNS, the probability was 7% for lysine and 0–2% for the other amino acids. The median (interquartile range) DIAAS for complementary food with and without LNS was 0.70 (0.28) and 0.64 (0.32), respectively. Dietary amino acid intake and protein quality were not significantly associated with length gain velocity from 6 to 12 months even after adjusting for confounding factors. Conclusions: The prevalence of inadequate amino acid intake in 9–10 months old infants in rural Malawi is very low. However, in conditions of frequent clinical or sub-clinical infections this situation may be different. Linear growth at 6–12 months does not appear to be limited by dietary amino acid intake or protein quality in this setting. Funding Sources: The Bill & Melinda Gates Foundation.